2006
DOI: 10.1002/mabi.200600228
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Poly(N‐propargylamide) with Galactose and Lauryloyl Groups: Synthesis and Properties

Abstract: An amphiphilic poly(N-propargylamide) with galactose and lauryloyl groups was synthesized by copolymerization of the corresponding N-propargylamide monomers using a Rh catalyst. The obtained copolymer formed a one-handed helical conformation and molecular aggregates in water. The observations by fluorescence microscopy in a cell culture experiment in the presence of dye-labeled copolymer indicated that the copolymer was incorporated into the cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…For this assumption, specific investigations provided support. Both our additional experiments (Scheme S1 and Figure S11) and early report 49 proved that alkynylated glucose played the role of "sergeants" in driving the soldiers (achiral monomer M units) to arrange in the identical helicity along the copolymer chains. Thus, our investigations demonstrated that the molecular chirality of the glucose units in the alkynyl-CNCs served as the chiral origin, while the rodlike structure of alkynyl-CNCs played the role of stabilizing agent for forming the optically active microparticles.…”
Section: ■ Results and Discussionmentioning
confidence: 52%
“…For this assumption, specific investigations provided support. Both our additional experiments (Scheme S1 and Figure S11) and early report 49 proved that alkynylated glucose played the role of "sergeants" in driving the soldiers (achiral monomer M units) to arrange in the identical helicity along the copolymer chains. Thus, our investigations demonstrated that the molecular chirality of the glucose units in the alkynyl-CNCs served as the chiral origin, while the rodlike structure of alkynyl-CNCs played the role of stabilizing agent for forming the optically active microparticles.…”
Section: ■ Results and Discussionmentioning
confidence: 52%
“…As has been recently reported by Suenaga et al for a copolymer carrier featuring hydrophobic lauryloyl groups (45), cold temperature induces a remarkable decrease in the copolymer-rhodamine uptake, indicating that the polymer is internalized Via an endocytosis mechanism. After a 10 h incubation at 4°C, labeled copolymers observed near unlabeled rhabdites are probably endocytotic vesicles that are about to fuse with rhabdites (Figure 8a-c).…”
Section: Resultsmentioning
confidence: 73%
“…The structure of the copolymer (left) and (right) the SEM80 image of the aggregated polymer particles (Reprinted from Ref 97. with permission from John Wiley and Sons).…”
mentioning
confidence: 99%